EMPOWERING ESP LEARNERS THROUGH BUSINESS MEETING SIMULATIONS: INSIGHTS ON CHALLENGES AND OPPORTUNITIES - Sari, Latifa Ika; Sari, Ria Hermina; Amrullah, Yozar Firdaus (University of Kuningan, 2024)
In ESP courses, it is important to provide students with authentic and realistic learning activities to improve their communicative competence. This study explores students’ perceptions of the use of business meeting simulation in an ESP course. There are two research questions guiding this study (1) How do the students perceive the use of business meeting simulation in improving their communicative competence? (2) What obstacles are faced by students in conducting the business meeting simulation? This research was conducted at the Port and Shipping Management department of a maritime polytechnic in Indonesia. A questionnaire consisting of close-ended questions and open-ended questions was used to collect data. Twenty-four students in semester seven were involved in completing a questionnaire exploring their perceptions. The quantitative and qualitative data from the questionnaire were recapped and analyzed. The findings of the study showed that most students agreed that the activity of business meeting simulation can improve their communicative competence, especially politeness strategies and various expressions used in a meeting. The study also revealed the obstacles faced by students, i.e., lack of vocabulary mastery and low self-confidence, limited time for preparation, and problems with group work.